The role of total body irradiation (TBI) as a conditioning regime for paediatric acute lymphoblastic leukaemia: A discussion of the evidence. Issue 1 (February 2016) - Hill, G.; Meikle, D.
Abstract: Aim: The long term effects of TBI with children can be adverse and has resulted in a debate as to whether chemotherapy only based condition regimes could be used as an alternatives. The aim of this article is to critically evaluate the literature relating to the role of TBI as a conditioning regime in ALL in children, and if there are any alternatives to current practices or future developments. Method: Key databases were searched for terms: conditioning regimes, transplantation, TBI, whole body radiation, systemic irradiation, stem cell transplantation, hematopoietic stem cell, and transplant conditioning. Results: Thirteen research articles from a variety of publications and two guidance documents from several sources were uncovered for critical discussion. Discussion/conclusion: There is little evidence for chemotherapy only regimes in paediatric ALL, but the practice continues. Modulating doses to improve homogeneity and use of IGRT could hold a future solution to reducing long-term toxicity and maintain the efficacy of irradiation. Highlights: TBI regimes have adverse long term effects on development, particularly on growth. Chemotherapy only regimes have long term effects that impact on development. TBI is a superior to chemotherapy only conditioning regimes for paediatric ALL. Research is being undertaken to refine TBI techniques to reduce overall toxicity.